Development of planning and control systems for autonomous surface vehicle - Teo, James (Nanyang Technological University, 2023)
The marine industry uses unmanned surface vehicles (USVs) without an operator. The use of USVs for various tasks, including environmental monitoring, maritime security, and oil spill response, has grown due to technological advancement. Today's USVs can carry out duties without human assistance and are used in commercial and military applications. This project aimed to create the USV's planning and control system in preparation for the Maritime RobotX Challenge in 2022. It is an international competition that brings together universities and companies from all over the globe and fosters cross-cultural understanding. Six challenging jobs that call for various sensing and navigational techniques are given to the USV to complete. For the microcontroller to plan the USV's next waypoint and send voltage signals to the propellers, the perception team provides vision, GPS, and hydrophone data. The difficulties include navigating through gates, dodging obstacles, spotting marine life, watching light patterns, and docking in the appropriate bay. The USV uses joystick control with a graphic user interface for manual control and situational-based planning to achieve autonomous control. The report outlines the precise procedures followed to complete each challenging job and emphasizes accurate perception's importance to success.